The role of measurement in moral injury care: latent profiles on the moral injury and distress scale - Griffin, Brandon J.; Warner, Elise A.; McCue, Matthew L.; Pietrzak, Robert H.; McLean, Carmen P.; Norman, Sonya B.; Maguen, Shira (Frontiers in Psychiatry, 2026)
IntroductionAlthough studies of moral injury proliferated over the past decade, few studies have examined common moral injury symptom presentations.MethodsData were analyzed from a population-based sample (N = 645) of combat veterans, healthcare workers, and first responders. All participants endorsed exposure to a potentially morally injurious event (PMIE) and completed the Moral Injury and Distress Scale (MIDS).ResultsLatent profile analysis revealed three distinct symptom profiles based on MIDS items assessing psychological, emotional, social, and spiritual symptoms of moral injury. The majority of participants (74.7%, n = 482) reported minimal moral injury symptoms. Approximately one in five participants (20.2%, n = 130) endorsed moderate levels of moral injury symptoms, and one in twenty (5.1%, n = 33) reported severe moral injury symptoms. All participants with the severe profile screened positive for probable moral injury on the MIDS (score ≥ 27); however, 9.1% had scores within normal limits on measures of posttraumatic stress and depression. After adjusting for demographics, those with moderate or severe moral injury symptoms were more likely than those with minimal moral injury symptoms to be younger, have fewer years of education, and identify as Hispanic.DiscussionThese findings support the use of the MIDS in measurement-based care to identify distinct clinical presentations of moral injury, including those with moderate to severe presentations that warrant further evaluation and potentially treatment.